2019
DOI: 10.12669/pjms.35.5.837
|View full text |Cite
|
Sign up to set email alerts
|

The effect of short pregnancy interval on perinatal outcomes in Turkey: A retrospective study

Abstract: Objective: The aim of the study was to determine the effect of short pregnancy interval on perinatal outcomes. Methods: The research was a retrospective study. The material consisted of birth records of a state hospital for the last three years in Manisa in the western region of Turkey (2015-2017) (n:8961). The research population included women whose gestational interval was ≤two years and the gestational week was over 22 weeks (n:2089). Perinatal outcomes were assessed through preterm birth, stillbirth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
3
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 22 publications
2
3
0
2
Order By: Relevance
“…With an adequate birth interval, the mother will be able to replenish her nutrient stores which are essential for foetal growth [ 13 , 21 ]. The positive relationship between long birth interval and birth weight found in the present study is congruent with the findings of earlier studies [ 22 27 ].…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…With an adequate birth interval, the mother will be able to replenish her nutrient stores which are essential for foetal growth [ 13 , 21 ]. The positive relationship between long birth interval and birth weight found in the present study is congruent with the findings of earlier studies [ 22 27 ].…”
Section: Discussionsupporting
confidence: 93%
“…e positive relationship between long birth interval and birth weight found in the present study is congruent with the findings of earlier studies [22][23][24][25][26][27].…”
Section: E Association Of Birth Intervals With Birth Weightsupporting
confidence: 93%
“…Women who have shorter intervals between pregnancies may not have enough time for their bodies to fully restore their blood volume and iron stores before the next pregnancy. This can further contribute to the development of anemia ( 33 ).…”
Section: Discussionmentioning
confidence: 99%
“…However, studies have reported inconsistent nding regarding short birth interval as risk factor for preterm birth. Studies conducted in Turkey and China revealed that pregnancy interval of two years or shorter does not increase the risk of preterm birth (12,13).…”
Section: Introductionmentioning
confidence: 96%